2023
DOI: 10.5603/fm.a2022.0021
|View full text |Cite
|
Sign up to set email alerts
|

A new type of the coracobrachialis muscle

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Olewnik et al [ 18 ] described a unilateral four-headed CB (accessory heads of different origins) in coexistence with a split CP with an accessory apex and a tunnel formation created from the CB two heads for the passage of both MCN and MN [ 18 ]. Zielinska and Olewnik [ 20 ] presented a unilateral six-headed CB, and Filippou et al [ 13 ] identified a bilateral asymmetrical multiplication of the CB heads (a right-side six-headed CB in coexistence with a contralateral five-headed CB).…”
Section: Discussionmentioning
confidence: 99%
“…Olewnik et al [ 18 ] described a unilateral four-headed CB (accessory heads of different origins) in coexistence with a split CP with an accessory apex and a tunnel formation created from the CB two heads for the passage of both MCN and MN [ 18 ]. Zielinska and Olewnik [ 20 ] presented a unilateral six-headed CB, and Filippou et al [ 13 ] identified a bilateral asymmetrical multiplication of the CB heads (a right-side six-headed CB in coexistence with a contralateral five-headed CB).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we do not have much information about its innervation. There are reports on CL provided by MCN [ 9 , 18 , 32 ]. Because of that CL is a variant of CBM, we can expand our research for coracobrachialis muscle (CBM).…”
Section: Discussionmentioning
confidence: 99%